Effect of beta propiolactone on specific antibody measurements by ELISA. Issue 4 (April 1993) - Agbarakwe, A E; Misbah, S A; Griffiths, H; Chapel, H M
Abstract : Serum samples from 30 HIV seronegative patients were treated with beta propiolactone (BPL) to determine whether BPL interfaces with ELISA for specific antibodies against protein and carbohydrate antigens. BPL had no discernible effect on specific antibody measurements by ELISA. With the measuring need for specific antibody measurements in the management of HIV seropositive patients, it is reassuring that this laboratory safety measure does not impair the reliability of results.